2002
DOI: 10.1111/j.0014-3820.2002.tb00162.x
|View full text |Cite
|
Sign up to set email alerts
|

A Metapopulation Perspective on Genetic Diversity and Differentiation in Partially Self-Fertilizing Plants

Abstract: Abstract. Partial self-fertilization is common in higher plants. Mating system variation is known to have important consequences for how genetic variation is distributed within and among populations. Selfing is known to reduce effective population size, and inbreeding species are therefore expected to have lower levels of genetic variation than comparable outcrossing taxa. However, several recent empirical studies have shown that reductions in genetic diversity within populations of inbreeding species are far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 42 publications
(54 reference statements)
8
137
0
Order By: Relevance
“…Thus reductions in diversity in selfing versus outcrossing populations were beyond that expected from the effect of the selfing rate alone at GapC3. These findings are consistent with predictions of the background selection hypothesis, but selective sweeps (Maynard Smith and Haigh 1974), consequences of metapopulation dynamics (Ingvarsson 2002), and past population bottlenecks cannot be completely ruled out.…”
Section: Pattern Of Nucleotide Polymorphism At Gapc3supporting
confidence: 86%
See 1 more Smart Citation
“…Thus reductions in diversity in selfing versus outcrossing populations were beyond that expected from the effect of the selfing rate alone at GapC3. These findings are consistent with predictions of the background selection hypothesis, but selective sweeps (Maynard Smith and Haigh 1974), consequences of metapopulation dynamics (Ingvarsson 2002), and past population bottlenecks cannot be completely ruled out.…”
Section: Pattern Of Nucleotide Polymorphism At Gapc3supporting
confidence: 86%
“…Levels of genetic diversity may result from the action of several factors, including population history, mating system, and direct selection, as well as selection at linked sites. Population history can exert strong effects on levels of DNA polymorphism-for instance, recent extinction and colonizing events (Ingvarsson 2002) and unequal contribution of migrants between demes in subdivided populations (Nagylaki 1982(Nagylaki , 2000Whitlock and Barton 1997) may also reduce effective population size and thereby lead to loss of population genetic variation at neutral loci. The mating system may also contribute to levels of population genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In the level of variation should be lower in the inbreeding than in the outbreeding species (Pollack 1987; Nordborg absence of population extinction (appendix, Equation A3), the expected ratio is approximated by the expresand Donnelly 1997). Indeed, Ingvarsson (2002) has shown that the ratio of within-population genetic diversion ( 1 ⁄ 2 M ϩ 1)/(M ϩ 1), where M is the population migration parameter 4Nm. A twofold reduction would sity in selfing vs. outbreeding species is much lower in structured populations.…”
Section: Estimates Of Population Parameters In Species Comparisonsmentioning
confidence: 99%
“…by the structure of the populations. Indeed, total levels of variation could be quite similar in selfing and in High levels of inbreeding are thus expected to increase the effects of genetic hitchhiking accompanying selecoutcrossing species if migration and effective population size are much lower in inbreeding species than in tive sweeps (Maynard Smith and Haigh 1974;Kaplan et al 1989) and background selection (Charlesworth outcrossing species (Ingvarsson 2002). …”
Section: Estimates Of Population Parameters In Species Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation